2017
DOI: 10.18632/oncotarget.14644
|View full text |Cite
|
Sign up to set email alerts
|

A new semisynthetic cardenolide analog 3β-[2-(1-amantadine)- 1-on-ethylamine]-digitoxigenin (AMANTADIG) affects G2/M cell cycle arrest and miRNA expression profiles and enhances proapoptotic survivin-2B expression in renal cell carcinoma cell lines

Abstract: Cardiac glycosides are well known in the treatment of cardiovascular diseases; however, their application as treatment option for cancer patients is under discussion. We showed that the cardiac glycoside digitoxin and its analog AMANTADIG can inhibit the growth of renal cell carcinoma (RCC) cell lines and increase G2/M cell cycle arrest. To identify the signaling pathways and molecular basis of this G2/M arrest, microRNAs were profiled using microRNA arrays. Cardiac glycoside treatment significantly deregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…However, especially for the Caki-1 renal cell carcinoma cell line and the PC3 prostate cancer cell line, GEV (4) was the most bioactive and cytotoxic compound. It was already shown that cardiac glycosides might have a different impact on various cancer cell lines [36]. In case of, non-small cell lung cancer A549 cells, EV seems a very promising candidate [12], and a well-established synthesis for this compound is an additional advantage of this study.…”
Section: Reactionmentioning
confidence: 80%
See 3 more Smart Citations
“…However, especially for the Caki-1 renal cell carcinoma cell line and the PC3 prostate cancer cell line, GEV (4) was the most bioactive and cytotoxic compound. It was already shown that cardiac glycosides might have a different impact on various cancer cell lines [36]. In case of, non-small cell lung cancer A549 cells, EV seems a very promising candidate [12], and a well-established synthesis for this compound is an additional advantage of this study.…”
Section: Reactionmentioning
confidence: 80%
“…The effect of the synthesized EV (2), GEV (3), and N-GEV (4) on the viability of renal cell carcinoma (Caki-1, 786-O) and prostate cancer (DU-145 and PC3) cell lines was investigated and compared to DTG (1) determined by [35,36]. All cardiac glycosides exhibited cytotoxic effects against renal and prostate cancer cell lines (▶ Table 2), however, they differed in their impact on the investi-gated cell lines.…”
Section: Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The key pathway associated with the Hoxa del signature was transcriptional misregulation in cancer. Several drugs with anti-cancer properties reported for solid tumors including, Mefloquine in glioblastoma [47], Digitoxigenin in renal carcinoma [48] and Emetine in bladder cancer [49] were associated with the Hoxa del signature. Furthermore, some of these drugs e.g., Emetine and Cephaline were recently shown to be highly active against primary chronic lymphocytic leukemia cells by repressing HIF-1α and disturbing intracellular redox homeostasis [50].…”
Section: Discussionmentioning
confidence: 99%